RELEVANSI KANDUNGAN INFORMASI ANTARA CASH FLOW DAN EARNINGS PADA PERUSAHAAN YANG MENGALAMI FASE DECLINE - Lies Nurhaini; Y Anni Aryani; Anas Wibawa (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2012)
Statement in the financial press and recent research suggest that controversy exist as to which accounting measure is more value-relevant: earnings or cash flow. This study examines the relative value relevance of earnings and cash flow measures in decline stage of a firm. Another aim of this study is to predict financial distress condition in that stage. Cash flow is expected to be more valuerelevant in the decline stage. In addition, it is argue that the firms in the decline stage are predicted having financial distress. The analysis sample consists of 30 firms in the decline stage. The entire sample member listed on the Indonesian Stock Exchange (IDX) during the period of 2007-2010 is selected using purposive sampling method. Evidence supports the hypothesis that cash flow is more value-relevant than earnings. Another result of this study shows that just 11 from 30 firms in the decline stage experience financial distress condition.Keywords: decline, value relevance, cash flow, earnings, financial distress